Spanish journals in WoS - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2010)
The number of Spanish journals indexed in the database Web of science is analyzed. It has grown from 44 in 2005 to 149 in 2009. Yet it seems that Spain is not adequately represented in relation to its scientific and publishing potential. The Spain presence in Scopus is considerably larger, with 223 journals.
Keywords: Web of science; Scopus; Spanish journals; Spain; Scientific journals.